Effect of training with the gradual distance drill method on the shooting skills of pétanque players - Mirop, Dominggus; Satria, M. Haris (Physical Education Departement of University PGRI Jombang, 2024)
Shooting ability in petanque sports is an important aspect that affects the performance of athletes. The phased distance drill method is very effective in improving skills in various sports areas. The problem lies in the effectiveness of the gradual distance drill training model to enhance the shooting ability of petanque athletes in the Tebedak petanque Club. The research method used an experimental approach one group pretest-posttest Design. The experiment will last about 6 weeks at a frequency of 3 workouts a week. The sample totaled 12 athletes. Inturmen research using test Shooting Game station 1 to station 5 with distance increments of 6,7,8, and 9 meters. Data were collected through direct observation of athletes ' training before and after training. Data analysis using SPSS version 23 to measure pretest and posttest. The results showed a significant effect of gradual distance drill method training on improving the shooting ability of petanque athletes in Tebedak petanque Club. Training summary the gradual distance drill method is very effective in improving the shooting ability of petanque athletes. The next research can pay attention to the drill training model to design a petanque athlete training program in other clubs.